PENEGAKAN HUKUM PIDANA TERHADAP KERUSAKAN LINGKUNGAN OLEH PERTAMBANGAN EMAS TANPA IZIN DIKABUPATEN MERANGIN - Permata, Hani Alisia; Ismed, Mohamad; Basuki , Basuki (CORPUS JURIS : JURNAL ILMU HUKUM, 2025)
Research Objectives: 1) To examine and analyze the handling of illegal gold mining (PETI) perpetrators who cause environmental damage. 2) To examine and analyze law enforcement against PETI perpetrators by prioritizing the restoration of the resulting environmental damage. Research Methods: This research employs a normative legal research method with several approaches: the statute approach, conceptual approach, analytical approach, philosophical approach, and case approach.Research Results: The Indonesian Forum for Environment (WALHI) of Jambi Province stated that as of 2025, the forest area damaged by illegal gold mining in Merangin is estimated to exceed 17,936 hectares. The handling of PETI perpetrators by the Merangin Regency Government, the Police, and the Governor of Jambi has not been optimal, despite the issuance of the Governor of Jambi's Circular Letter No. 414/491/DPMD/2025 regarding PETI. Law enforcement against PETI perpetrators has not yet achieved the three fundamental legal pillars: legal certainty (rechtssicherheit), utility (zweckmassigkeit), and justice (gerechtigkeit). This is due to several factors: a) the legal substance governing PETI, b) the lack of firmness among law enforcement officials, and c) the legal culture of the community regarding PETI activities, while law enforcement facilities remain adequate. Criminal sanctions for PETI are regulated under Article 158 of Law No. 3 of 2020 concerning Mineral and Coal Mining, which carries a maximum penalty of 5 (five) years imprisonment and a maximum fine of IDR 100 billion. Based on Article 80 paragraph 1 letter (a) of the Criminal Procedure Code (KUHAP) under Law No. 20 of 2025, PETI perpetrators may pursue Restorative Justice. While Restorative Justice in ordinary crimes involves a settlement between the victim and the perpetrator, in environmental crimes committed by PETI, Restorative Justice can be facilitated through environmental Non-Governmental Organizations (NGOs), following the doctrine of Christopher Stone. There is a pressing need for government regulations to determine who represents the environment as a legal subject and how fines can be distributed for post-mining reclamation.